2012
DOI: 10.1007/s13147-012-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Klimaanpassung auf regionaler Ebene: Herausforderungen einer regionalen Klimawandel-Governance

Abstract: Zusammenfassung Die Region ist die zentrale Raumeinheit für die Umsetzung von Klimaanpassungsstrategien. Sie umfasst die funktionsräumliche Dimension der meisten Klimawandelfolgen und ist damit die geeignete Maßstabsebene für kooperative Regierungsformen, eine flexible rechtliche Steuerung, institutionelle Innovationen und kollektive Konfliktlösungen. Wie diese konkret gestaltet sein sollten ist bisher nur in Ansätzen geklärt. In der noch jungen Klimaanpassungsforschung steht die Aufmerksamkeit für Querschnitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A large proportion of such academic discussions are characterised by an approach predominantly derived from the natural sciences, delivering mostly technical proposals for coping with changes in climate and vulnerability (Cannon and Müller-Mahn, 2010;Grießhammer et al, 2012:3). Additionally, this often involves asking how actions of city governments can be better organised and coordinated, and which actors do/should participate in the actual processes of urban development in order to improve and optimise governance processes (Baasch et al, 2012;Birk et al, 2011;Klemme and Selle, 2010). From a political-geographical perspective, two aspects in particular, which are crucial for the transformation of energy-and climate-relevant policies, are left out of consideration: first, the question of why, despite broad support, policy contents have been implemented to such varying degrees in different cities; and second, what conflicts and discursive negotiation processes emerge on the urban scale while energy and climate policies are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of such academic discussions are characterised by an approach predominantly derived from the natural sciences, delivering mostly technical proposals for coping with changes in climate and vulnerability (Cannon and Müller-Mahn, 2010;Grießhammer et al, 2012:3). Additionally, this often involves asking how actions of city governments can be better organised and coordinated, and which actors do/should participate in the actual processes of urban development in order to improve and optimise governance processes (Baasch et al, 2012;Birk et al, 2011;Klemme and Selle, 2010). From a political-geographical perspective, two aspects in particular, which are crucial for the transformation of energy-and climate-relevant policies, are left out of consideration: first, the question of why, despite broad support, policy contents have been implemented to such varying degrees in different cities; and second, what conflicts and discursive negotiation processes emerge on the urban scale while energy and climate policies are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of personal experience is highlighted by many authors, be it experience-based knowledge leading to certain tree species choices (Lidskog and Sjödin 2014) or prior experience with hazards or extreme weather. Evidence of the notion that Bseeing is believing^comes from many scientific fields (Weber 2016) and it has been shown that people from regions that have experienced only few extreme weather events in the recent past were less aware of global climate change than those who had frequent experience (Baasch et al 2012). The idea that experience leads to action is highlighted in many studies on climate change perception (Joireman et al 2010;Wachinger et al 2013) but also in forest science specifically (Blennow et al 2012;Seidl et al 2016;Sousa-Silva et al 2016).…”
Section: Approaching Climate Change Awarenessmentioning
confidence: 99%
“…Climate change is playing an increasingly important role in spatial planning research. This is especially true for Germany, where 70% of the population live in cities [1][2][3][4][5][6]. Positive migration rates into cities mostly stem from better job opportunities and better functioning infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Research thus far has paid little attention to how different stakeholders perceive and assess green and open spaces. Citizens, politicians, planning administrations, and external service providers are all involved in planning and implementation processes, albeit to varying extents [3]. A deeper understanding of which perceptions these stakeholders hold, as well as the associated procedural conflicts between them, is crucial, but thus far lacking.…”
Section: Introductionmentioning
confidence: 99%